2022
DOI: 10.1021/acs.inorgchem.2c01106
|View full text |Cite
|
Sign up to set email alerts
|

Transient Radiation-Induced Berkelium(III) and Californium(III) Redox Chemistry in Aqueous Solution

Abstract: Despite the significant impact of radiation-induced redox reactions on the accessibility and lifetimes of actinide oxidation states, fundamental knowledge of aqueous actinide metal ion radiation chemistry is limited, especially for the late actinides. A quantitative understanding of these intrinsic radiation-induced processes is essential for investigating the fundamental properties of these actinides. We present here a picosecond electron pulse reaction kinetics study into the radiation-induced redox chemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 69 publications
1
15
0
Order By: Relevance
“…• radicals: k = (2.07 ± 0.43) × 10 8 and (1.78 ± 0.19) × 10 8 M −1 s −1 , respectively. 12 Consequently, oxidation by the Cl 2…”
Section: Chemical Kinetics For the Reaction Of Thementioning
confidence: 99%
See 2 more Smart Citations
“…• radicals: k = (2.07 ± 0.43) × 10 8 and (1.78 ± 0.19) × 10 8 M −1 s −1 , respectively. 12 Consequently, oxidation by the Cl 2…”
Section: Chemical Kinetics For the Reaction Of Thementioning
confidence: 99%
“…This additional species was not evident in the absence of Cf 3+ ions, nor can it be attributed to the Cf 4+ oxidation product, as this species has only minimal absorption at 450 nm. 12 A potential candidate for this species is the oxygen adduct of the persulfate peroxyl radical anion,…”
Section: Chemical Kinetics For the Reaction Of Thementioning
confidence: 99%
See 1 more Smart Citation
“…The presented findings are expected to apply for other trivalent minor actinides (e.g., curium, berkelium, and californium) and lanthanides, whose di-and tetravalent states are typically transient without additional stabilization. 51,52 That said, ongoing research is investigating the combined impact of radiolysis and redox chemistry by using earlier actinides, such as uranium, neptunium, and plutonium. 53 These elements have access to a wider range of stable oxidation states that may facilitate additional inner vs outer sphere chemistry in the corresponding HOPO complex.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…However, this would entail the formation of thermodynamically unfavorable di- and tetravalent lanthanide and transplutonium oxidation states. Concerning the latter, electron pulse irradiation studies have demonstrated the transient formation of some of these nontraditional valence states seen in the noncomplexed metal ion. , For example, trivalent curium has been shown to undergo radiation-induced redox processes to yield the corresponding di- and tetravalent states, both of which exhibited lifetimes on the order of tens of microseconds. , This is more than sufficient time to promote changes in their coordination environments and propagate the radiation chemistry.…”
Section: Introductionmentioning
confidence: 99%